Can Broadly Neutralizing HIV-1 Antibodies Help Achieve an ART-Free Remission? - Hsu, Denise C.; Mellors, John W.; Vasan, Sandhya (Frontiers in Immunology, 2021)
Many broadly neutralizing antibodies (bnAbs) targeting the HIV-1 envelope glycoprotein are being assessed in clinical trials as strategies for HIV-1 prevention, treatment, and antiretroviral-free remission. BnAbs can neutralize HIV-1, target infected cells for elimination, and stimulate host anti-HIV-1 immune responses. Concerns about HIV-1 resistance to single bnAbs have led to studies of bnAb combinations with non-overlapping resistance profiles. This mini-review focuses on the potential for bnAbs to induce HIV-1 remission, either alone or in combination with latency reversing agents, therapeutic vaccines or other novel therapeutics. Key topics include preliminary activity of bnAbs in preclinical models and in human studies of HIV-1 remission, clinical trial designs, and antibody design strategies to optimize pharmacokinetics, coverage of rebound-competent virus, and enhancement of cellular immune functions.